Hydrogen sulfide: A new therapeutic target in vascular diseases - Zhu, Cuilin; Liu, Qing; Li, Xin; Wei, Ran; Ge, Tongtong; Zheng, Xiufen; Li, Bingjin; Liu, Kexiang; Cui, Ranji (Frontiers in Endocrinology, 2022)
Hydrogen sulfide (H2S) is one of most important gas transmitters. H2S modulates many physiological and pathological processes such as inflammation, oxidative stress and cell apoptosis that play a critical role in vascular function. Recently, solid evidence show that H2S is closely associated to various vascular diseases. However, specific function of H2S remains unclear. Therefore, in this review we systemically summarized the role of H2S in vascular diseases, including hypertension, atherosclerosis, inflammation and angiogenesis. In addition, this review also outlined a novel therapeutic perspective comprising crosstalk between H2S and smooth muscle cell function. Therefore, this review may provide new insight inH2S application clinically.